Examining the Objectives and Process of EFL University Students When Conducting Self-Directed Learning with Duolingo: A Narrative Inquiry - Aziz, Kasyfil; Saefullah, Hilmansyah (Regalia Institute, 2024)
Students must engage in independent study as one of the strategies that promotes student-centered learning since it affects how they learn. Some students rarely engage in independent learning, such as SDL, since they lack motivation, particularly when it comes to learning English. The purpose of this study is to look into how four college students use Duolingo for self-directed learning (SDL) and evaluate the objectives and procedure. A narrative inquiry was employed in this study to elucidate participant experiences. Additionally, data were gathered through semi-structured interviews and daily journals kept by the students. The journal was the first tool employed, and the initial data was collected seven times. To confirm or supplement the information from the journals, all participants were questioned after the journals had all been gathered. Thematic analysis was used to examine the data. The study demonstrated that all participants could control the process of self-directed learning, define their own objectives and goals, and provide feedback on their SDL. Furthermore, because Duolingo has features that support all SDL procedures, adopting it as a tool or media for SDL helps participants feel more excited to participate in SDL. Key words: duolingo, independent learning, narrative inquiry, mobile assisted language learning, self-directed learning.